Factors predisposing to acquired von Willebrand syndrome during the course of polycythemia vera – retrospective analysis of 142 consecutive cases. Issue 4 (October 2015) - Mital, Andrzej; Prejzner, Witold; Świątkowska-Stodulska, Renata; Hellmann, Andrzej
Abstract Introduction The aim of this study was to verify if PV patients with and without avWS differ in terms of their baseline clinical parameters. Material and Methods The study included 142 consecutive patients with PV. avWS was diagnosed on the basis of abnormally low levels of von Willebrand factor and other routine tests. Patients with and without concomitant avWS were compared in terms of their demographic characteristics, present and past medical histories and laboratory parameters. Results Concomitant avWS was found in 17 PV patients (12.0%). Individuals with avWS have been diagnosed with PV at significantly younger age than those without, and significantly less often were in remission at the time of testing for bleeding disorders. Most of them (58.8%) presented with typical signs of bleeding disorder. Moreover, they showed significantly higher erythrocyte, leukocyte and platelet counts, abnormalities of coagulation profile corresponding to defects of primary hemostasis and abnormal values of all parameters used in the routine diagnosis of avWS. Conclusions Even every tenth patient with PV may develop avWS. Young age at diagnosis of PV and poor response to previous treatment of this condition are potential risk factors of avWS that should be considered during history taking. Sings of bleeding disorder observed in a person with PV necessitate evaluation for avWS.